Googling in anatomy education: Can google trends inform educators of national online search patterns of anatomical syllabi?. Issue 2 (22nd August 2016) - Phelan, Nigel; Davy, Shane; O'Keeffe, Gerard W.; Barry, Denis S.
Abstract : The role of e‐learning platforms in anatomy education continues to expand as self‐directed learning is promoted in higher education. Although a wide range of e‐learning resources are available, determining student use of non‐academic internet resources requires novel approaches. One such approach that may be useful is the Google Trends © web application. To determine the feasibility of Google Trends to gain insights into anatomy‐related online searches, Google Trends data from the United States from January 2010 to December 2015 were analyzed. Data collected were based on the recurrence of keywords related to head and neck anatomy generated from the American Association of Clinical Anatomists and the Anatomical Society suggested anatomy syllabi. Relative search volume (RSV) data were analyzed for seasonal periodicity and their overall temporal trends. Following exclusions due to insufficient search volume data, 29 out of 36 search terms were analyzed. Significant seasonal patterns occurred in 23 search terms. Thirty‐nine seasonal peaks were identified, mainly in October and April, coinciding with teaching periods in anatomy curricula. A positive correlation of RSV with time over the 6‐year study period occurred in 25 out of 29 search terms. These data demonstrate how Google Trends may offer insights into the nature and timing of online search patterns of anatomical syllabi and may potentially inform the development and timing of targeted online supports to ensure that students of anatomy have the opportunity to engage with online content that is both accurate and fit for purpose. Anat Sci Educ 10: 152–159. © 2016 American Association of Anatomists.